2017
DOI: 10.1016/j.amjms.2017.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Fanconi Anemia and Laron Syndrome

Abstract: To the best of our knowledge, this study is the first to suggest an association between FA and LS. We propose that IGF-1 administration might improve some FA complications and functions based upon IGF-1 beneficial actions observed in animal, cell and indirect clinical models: erythropoiesis modulation, immune function improvement and metabolic regulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…For Latin Americans, the E180 polymorphism is the most common due to a mass migration to Ecuador[21]; nevertheless, the E180 polymorphism has been found in Brazil, Argentina, and Mexican-descendants in the United States[4]. Recently, in Monterrey, Mexico, three patients were identified with LS, and the key mutations that were identified as possible causes were not of GHR[5-7]. Here, we demonstrate that the LS in the parents was associated with the del5-6 of GHR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For Latin Americans, the E180 polymorphism is the most common due to a mass migration to Ecuador[21]; nevertheless, the E180 polymorphism has been found in Brazil, Argentina, and Mexican-descendants in the United States[4]. Recently, in Monterrey, Mexico, three patients were identified with LS, and the key mutations that were identified as possible causes were not of GHR[5-7]. Here, we demonstrate that the LS in the parents was associated with the del5-6 of GHR.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of Laron syndrome (LS), first described in 1966[1] as insensitivity to growth hormone (GH) due to mutations in the extracellular domain of the GH receptor (GHR)[2,3], is not commonly diagnosed in Latin America. Moreover, in Mexico, there are less than 10 documented cases of LS[4-7]. LS is typically found among the Jewish community[8], but with a very low prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…This is the case in Mexico, where our group has found patients with de visu diagnosis. Some of them are still being confirmed, while others have been published .…”
Section: Discussionmentioning
confidence: 97%
“…During development, the establishment of a proper intrauterine environment for fetal development is mandatory, a situation where IGF-1 plays a key role. To date, several case reports in women have shown that partial IGF-1 deficiency might be involved in alterations in the reproductive system and the attainment and maintenance of pregnancy [ 38 , 39 , 40 ], and also its implications in metabolism, which could alter the metabolism of xenobiotic substances such as ethanol. For this reason, the development of an animal model that resembles the physiological alterations due to partial IGF-1 deficiency is crucial for studying the mechanisms and molecular targets involved in its development, especially in critical periods such as pregnancy.…”
Section: Discussionmentioning
confidence: 99%